Hacking Product Design A Guide to Designing Products for Startups - Jing, Tony (Apress, 2018)
Understand how designing a technology product in a startup environment is markedly different from product design at established companies. This book teaches product designers how to think and frame problems in the dynamic context of startups. You will discover how to enhance your soft skills that are often not taught, but are crucial to your success. In the emerging field of design for technology products, there are many books and resources covering the hard skills-such as visual design, interface design, prototyping, and motion design. These skills are necessary to design work; however, without an understanding of the true potential of design and the skills required to unleash that potential in a startup setting, the impact of design may remain at a production level and not reach a position where it can positively impact product strategy and the business bottom line. Hacking Product Design addresses that gap in knowledge. What You'll Learn: Gain foundational knowledge: know what startups are, the mindset designers should have when working in startups, and how to solve problems Generate product ideas, collaborate with others, and prioritize what to do to maximize the potential of those ideas Discover how to be successful in designing great products-know what to focus on and the principles to follow.